Upaya Peningkatan Aktivitas Belajar Sejarah Siswa Melalui Pembelajaran Cocoperatif Learning Tipe Snowball Throwing di Kelas XI IPS 3 SMA Negeri 1 Pasaman - Erniwati Erniwati (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2015)
Based on observation in field students are less active learning history, they are lazy to do assignment, after getting out the class, sometimes even fall a sleep whily studying. Those have an imfact on their learning out comes which are not maximum or lower. The low comes student learning are caused by some factors, one of them is improperly choosing learning method, which tend to be monotonous and learning is dominated by teachers only. The aims of this research is to know, how far cooperative learning snowball throwing type can improve students learning activity in history lesson. The type of research is action class at XI IPS 3 class SMAN 1 Pasaman. The implementation consist of 2 cycles are planning, implementation, observation  and reflection. Techniques data analysis is carried out using the formale techniques proportion by Sudjana. Success indicators are determined by Ari kunto refence and studien`s negative activite is determined by slameto refrence. Result of the analysis first cycle and second cycle show students learning active ty has increased for all indicators that is actively discussing (good 56,1 %), responding questions (good 56,3%), questioning  based on material (good 68,7 %), cooperation on group (good 61,8%)  and taking conclusion (good 65%), while negative activites are decrease such as less aftention (good 6,5 %), distributing of friends (good 0,0%) and frequently ask permission (good 0,0%). Increasing student learning out comes is also good in the first cycle, averagevalue 76,3 (classical competences 68 %) and the second cycle average value 8,2 (classical   85%). There was increase 6,07 for student learning out comes and 17  percentage master learning classically. The result of the research learning model through Cooperative learning Snowball throwing type can increase student learning activities in history class at XI IPS3 student SMAN I  Pasaman. So this method can applied as aneffort to increase student learning activities, because there is no methods most superior from the existing method, each of them has weaknesses and advantages.